Kajian Smart Contract Dalam Perspektif Hukum Positif Di Indonesia - Adam Muko (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
In the era of technology 4.0, Indonesia is pursuing progress through the adoption of smart contracts on the blockchain. The government responded to this by establishing technology regulations to address emerging challenges. Legal principles demonstrate their adaptability in the digital era by utilizing information technology to build a modern legal and administrative framework, in line with the vision of industrial development 4.0. This normative juridical legal research evaluates the application of legal norms in a concrete context, using statutory and conceptual approaches. Data collection was carried out through literature study using primary, secondary and tertiary legal materials. Data analysis uses qualitative descriptive methods. Smart contracts are increasingly widely used, especially in electronic transactions such as stock trading, crypto and hotel reservations. As a form of electronic agreement, smart contracts facilitate the automation of contract processes. However, its use must comply with the law and technology neutral principles in the ITE Law. Even though it is automatic, this technology is recognized as an Electronic Agent in accordance with Article 1 Number 8 of the ITE Law. The validity of these automated contracts is only questioned if it is proven that the automated system is problematic. Smart contracts in Indonesia are recognized in the context of contract law based on freedom of contract and the legal basis of the Civil Code. This recognition occurs because the Civil Code is open and complementary. However, the use of smart contracts must comply with statutory regulations, principles of decency and public order. Regulations governing smart contracts include the ITE Law, PP PTSE, and PP PMSE. These three regulations stipulate the procedures for using electronic contracts, providing a clear legal basis for the implementation of smart contracts.